Comparing intentional vocabulary learning strategies of rote-copying versus read-plus - Wong, Sze Wei; Anie Attan, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The purpose of this within-group experimental study was to compare the effectiveness of treatment on vocabulary acquisition and retention using two explicit vocabulary learning strategies (VLS) of Rote-Copying (RC) and Read-Plus (RP). Thirty five Form 1 Malaysian secondary school learners with poor English proficiency participated in both treatments for two weeks with each treatment carried out once in each week. A post-test was administered a week after the treatments. Participants read adapted texts and underwent different treatments. The RC required participants to copy L2 words, sentence in context and their translated L1 equivalent twice; while three vocabulary enhancement activities were used in RP. Nation’s 1000 Level Vocabulary Test was used in this study. Results indicate that there was no significant difference between RC and RP in vocabulary learning. Both treatments led to significant vocabulary learning, however, participants showed better vocabulary gain in the post-test after undergoing the RP treatment. Interview findings indicate that participants preferred the more cognitively-challenging RP treatment. In contrast, the RC was deemed boring and ineffective. Nevertheless, RC was useful for low proficient ESL learners. In sum, intentional VLS seemed to be the key to vocabulary learning.